Cleanzee Toilet Brush: Electric Toilet Brush with Disinfectant Holder / Nur Fitriani Mohd Amin - Mohd Amin, Nur Fitriani (2020)
This report is about an innovation of a toilet brush. In this era especially with the pandemic covid-19 outbreak, people always care about cleanliness of a toilet, be it at home or the public toilet. In order to make sure they used only the clean and germ-free toilet, they need to care about the hygiene. Different from the existing toilet brush, this new product has come out with the electric toilet brush with disinfectant holder, named Cleanzee toilet brush. Cleanzee toilet brush is a smart electronic toilet brush that is cordless and powered by 2 D batteries that can last up to 3 hours of usage per day. The brush bristles are made of silicone which is a very flexible material that will make it easier to reach and slide to the curvy area of every toilet bowl. The brush also comes with a chemical dispenser so that user can directly sprays the chemical from the brush handle and clean the toilet bowl instantly. Other than that, the brush also comes with a disinfectant holder where it disinfects while holds the brush steadily and it then can be safely placed anywhere around the toilet. Cleanzee toilet brush is the product that has been targeted some group of people such as household managers, usually housewives or maids and cleaning services company. By purchasing this product, the toilet cleaning chores will be easy, effortless and efficient. This is because the Cleanzee toilet brush not only cleans and scrub the toilet bowl automatically, it also disinfects the brush after usage so that the brush is hygienic and safe to be used next time.